Hepatic Dysfunction in Dengue Fever and Dengue Hemorrhagic Fever: A Cross-Sectional Study at a Tertiary-level Hospital (Central Medical College Journal, 2025)
Background: Dengue is the most prevalent mosquito-borne viral infection, endemic in South-East Asia   and found in tropical and subtropical regions worldwide, predominantly in urban and peri-urban areas. In   Bangladesh, dengue has emerged as a significant public health concern since the mid-2000s. Beyond   classical presentations, many patients with dengue infection present with liver dysfunction. Objective: The   general objective of this study was to assess changes in liver function (AST, ALT, PT) in Dengue Fever   (DF) and Dengue Hemorrhagic Fever (DHF). The specific objective was to evaluate whether changes in   liver function could predict disease severity. Study Design and Method: This cross-sectional study was   conducted over six months in the Medicine Wards of Sir Salimullah Medical College and Mitford Hospital,   Dhaka, and included 50 patients diagnosed with DF or DHF. Results: Among the 50 patients, 34 (68%)   had DF and 16 (32%) had DHF. Overall, 42% of patients had elevated AST and ALT levels. Most patients   (58%) had AST and ALT levels within group 1 (≤46 U/L). AST elevation was observed in 32%, 4%, and 6%   of patients in groups 2 (47–120 U/L), 3 (121–200 U/L), and 4 (>200 U/L), respectively. ALT elevation was   observed in 26%, 10%, and 6% of patients in groups 2, 3, and 4, respectively. Elevated ALT levels were   more frequent in DHF compared to DF, with a statistically significant difference (p1 mg/dL in 18.75% of DHF patients compared to 6% of DF patients. Prothrombin time (PT) was   prolonged by more than 3 seconds in 4 of 34 DF patients (11.76%) and in 6 of 16 DHF patients (37.5%),   which was also statistically significant (p